Analysis of the Implementation of PSAK 73 on Finance Leases on Financial Performance - Anwar, Muhammad Faishol; Indah, Djunita Permata; Muhsin, Muhsin (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the impact of PSAK 73 on the financial performance of state-owned companies in Indonesia's energy, oil, and gas sectors. Using a quantitative approach, secondary financial data from PT Pertamina and PT PLN for the period 2018-2021 were analyzed. The analysis focuses on solvency ratios, specifically the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), as well as profitability ratios, including Return on Assets (ROA) and Return on Equity (ROE). The findings indicate that after the implementation of PSAK 73, both PT Pertamina and PT PLN experienced an increase in the DER and DAR ratios, signifying a higher reliance on liabilities for operational financing. PT Pertamina saw a 1.5% increase in its DAR, while PT PLN's DAR increased by 0.5%. However, profitability ratios displayed mixed results: PT Pertamina's ROA and ROE decreased by 2.07% and 4.2%, respectively, while PT PLN showed a modest increase of 0.5% in ROA and 0.1% in ROE. These results suggest that PSAK 73 had a notable impact on the companies’ solvency but had a varied effect on profitability. The study aligns with prior research on PSAK 73’s effects, particularly on solvency, while profitability results differ across sectors.